(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Shiva Trilogy, a renowned work of mythological fiction authored by Amish Tripathi, reimagines the legend of Lord Shiva. The series comprises three books: The Immortals of Meluha, The Secret of the Nagas, and The Oath of the Vayuputras. These books chronicle the expedition of Shiva, a tribal chief originating from the mountainous regions who is revered as the foretold Neelkanth, the deity associated with annihilation. General Parvateshwar, Shiva’s devoted spouse and spouse Sati, is among the characters introduced in the novels who assume pivotal positions in the narrative. Nonetheless, the series also features several neglected combatants whose contributions are vital to the narrative but frequently go unacknowledged. Tripathi adeptly examines the motif of the neglected combatants in this grand epic narrative, a recurring theme that permeates the entirety of the trilogy. The novel envisions the protagonist, Shiva, as a warrior deity whose advent signifies the commencement of a prosperous and tranquil epoch in the city of Meluha. Nevertheless, the novel also offers a less refined perspective on the social hierarchy of Meluha, specifically concerning the neglected combatants of the Naga tribe. In analysing the Shiva Trilogy’s depiction of the forgotten characters, this paper will examine the author’s various approaches to introducing, exploring, and representing this theme. The purpose of this research is to examine the importance of these neglected personas within the Shiva Trilogy.